Development of Biodegradable Materials for Consumer Product Packaging: Environmental Impact and Consumer Preferences - Anggraini, Welly (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Conventional plastics significantly contribute to environmental pollution due to their non-biodegradable nature. Eco-friendly alternatives such as biodegradable materials are being developed to mitigate these negative impacts. This study employs a mixed-method approach with three main phases: (1) exploration and characterization of biodegradable materials based on polylactic acid (PLA) and corn starch; (2) environmental impact analysis using Life Cycle Assessment (LCA) to evaluate carbon footprint and energy consumption; and (3) consumer preference surveys through questionnaires and interviews in Bandar Lampung. The results indicate that biodegradable materials exhibit higher biodegradability and lower environmental impact than conventional plastics. LCA analysis demonstrates that these materials reduce carbon emissions and energy consumption. Despite challenges such as production costs and material durability, most consumers in Bandar Lampung prefer environmentally friendly packaging. This study provides insights into the potential implementation of biodegradable materials in Indonesia and their contribution to sustainable solutions in the packaging industry.